2015
DOI: 10.1074/jbc.m114.608273
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Daptomycin Gene Cluster in Streptomyces roseosporus by an Autoregulator, AtrA

Abstract: Background:No investigation on daptomycin production at the transcriptional regulatory level has been reported. Results: The autoregulator AtrA directly regulates daptomycin gene cluster expression, and atrA is the transcriptional target of AdpA. Conclusion:The AtrA-mediated transcriptional signaling pathway directly regulates daptomycin production. Significance: We reveal for the first time the transcriptional regulatory mechanism of daptomycin production for its potential rational genetic engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 27 publications
4
81
0
Order By: Relevance
“…Electrophoretic mobility shift assays (EMSAs) showed that DepR1 could specifically bind to dptEp and that this shift became even more significant as the amount of DepR1 was increased (Fig. 1C), which also was seen in other studies of, e.g., AtrA-dptEp interaction (21). Moreover, one binding site of DepR1 on dptEp was identified by DNase I footprinting assays ( Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Electrophoretic mobility shift assays (EMSAs) showed that DepR1 could specifically bind to dptEp and that this shift became even more significant as the amount of DepR1 was increased (Fig. 1C), which also was seen in other studies of, e.g., AtrA-dptEp interaction (21). Moreover, one binding site of DepR1 on dptEp was identified by DNase I footprinting assays ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…However, the binding sequence had no consensus with other TetR family regulators or apparent palindrome sequence, which often are recognized by TetR family regulators (35). However, this observation is not unique, since we had identified another TetR family regulator, AtrA, which binds to nonpalindrome sequence either on dptEp or its own promoter (21). These results confirmed DepR1 was a transcriptional regulator interacting directly with the promoter of the daptomycin gene cluster.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations